Schooling From Home During Pandemic: How Do Parents' Response Towards Online Learning? - Hesmatantya, Vega; Wijaya, Armeria (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2023)
This study aims to find the parents' response towards online schooling from home attended by their children. The spread of Covid-19 becomes a massive pandemic hazardous for the community. Its rapid transmission forces government to implement emergency policy to cope with this virus. The Ministry of Education and Culture decided to eliminate face-to-face learning on behalf of the Indonesian Government. The school is temporarily closed to disrupt a chain of Covid-19 transmission. As a replacement, face-to-face learning is transformed to be online learning. In this case, parents' roles become more prominent because they must provide learning assistance to their children to ensure that schooling from home can be followed properly. This exploratory research involved 200 parents as respondents to fill in the questionnaire, and later 12 parents were invited to proceed with further interview sessions. The result indicated a positive response to the implementation of online learning initiated by their schools. Its implementation is an appropriate option for preventing students from infectious Covid-19. However, some obstacles occur when parents cannot assist their children optimally due to their responsibility to accomplish their work and go to the office during school hours. It is suggested that teachers' assistance during learning from home can be improved to maintain effective learning. Moreover, parents hope that face-to-face school can be held right away after the pandemic is successfully handled.